2018
DOI: 10.1155/2018/7295131
|View full text |Cite
|
Sign up to set email alerts
|

Association of Three Polymorphisms rs11614913, rs2910146, and rs3746444 in miRNA-196a2, miRNA-146a, and miRNA-499 with Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: Background It has been found that single-nucleotide polymorphisms (SNPs) of microRNA might be involved in the development of inflammatory bowel diseases (IBDs). However, the related retrospective research has not been reported. In this work, we performed a meta-analysis to derive a more precise estimation of the associated relationship. Methods We searched the studies on the association of SNPs of microRNA with the hereditary susceptibility of IBD in PubMed and Embase; eligible research was selected by screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Liu et al performed a meta-analysis exploring the association of SNPs from miRNAs and IBD. They reported three polymorphisms (rs11614913, rs2910146, and rs3746444) in miRNA-196a2, miRNA-146a, and miRNA-499 in patients with IBD [ 121 ].…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
“…Liu et al performed a meta-analysis exploring the association of SNPs from miRNAs and IBD. They reported three polymorphisms (rs11614913, rs2910146, and rs3746444) in miRNA-196a2, miRNA-146a, and miRNA-499 in patients with IBD [ 121 ].…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
“…[11,12] In addition, another study demonstrated that rs2910164 was significantly associated with the susceptibility to inflammatory bowel disease. [13]…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al performed a meta-analysis exploring the association of SNPs from miRNAs and IBD. They reported three polymorphisms (rs11614913, rs2910146, and rs3746444) in miRNA-196a2, miRNA-146a, and miRNA-499 in patients with IBD [117]. In addition, other miRNAs expression profiles changed during IBD.…”
Section: Vitamin D/vdr Epigenetic Role In Ibdmentioning
confidence: 99%